Processo administrativo previdenciário: uma análise visando à efetividade - Araujo, Gustavo Beirão (2019)
This paper seeks to reflect on the role of the social security administrative process (PAP) in the concretion of the fundamental right to the benefits and services of social security. Because it is a theme that affects all of society in a significant way, it is intended to investigate, in accordance with the values that guide social security, how it can bring true effectiveness to the social security administrative process. The Federal Public Administration has a linked action, limiting the way the public agent acts in certain situations, which does not always contribute to the realization of rights. Departing from the concept of Social Security Law and its scope, the general aspects of the social security administrative process will be discussed, conceptualizing it, as well as the principles applicable to it. Next, the phases of the social security administrative process will be scrutinized, analyzing how the Administration and administered can contribute to the PAP being able to achieve its objective with the greatest effectiveness possible, within a scenario in which full effectiveness is not yet possible to be achieved. Finally, in light of the doctrine of post-positivism and the constitutionalisation of Law, proposals will be presented aiming at giving full effectiveness to PAP in the short, medium and long term